Experimental performance analysis of novel indirect-expansion solar-infrared assisted heat pump dryer for agricultural products - Singh A.; Sarkar J.; Sahoo R.R. (My University, 2025)
In the present study, a novel compact size convective batch-type solar-infrared assisted heat pump dryer is developed and experimentally investigated for closed air cycle drying of banana chips. Performances of four different operational modes of the system, simple heat pump drying, infrared-assisted heat pump drying, solar-assisted heat pump drying and solar-infrared-assisted heat pump drying are compared. Effects of drying time and product moisture content on various energetic and exergetic performance parameters are investigated. For all operational modes, the banana chips are dried to remove moisture from 83.8% to 11.5% at dryer inlet air velocity of 0.8 m/s. Both energy efficiency (58.5%) and exergy efficiency (24%) are found highest for solar-assisted heat pump dryer. The coefficient of performance is found highest for the simple heat pump dryer. The average moisture extraction rate is found highest (1.1618 kg/h) for solar-infrared-assisted heat pump dryer and lowest for the simple heat pump dryer. The specific moisture extraction rate is found highest for the solar-assisted heat pump drying and lowest in case of infrared-assisted heat pump drying. The present study shows the successful development of the combination of the different drying systems such as heat pump, solar and infrared in a single drying system for faster food chips drying. © 2020 International Solar Energy Society